Generalized Dual to Ratio-cum-Product Type Estimators in Double Sampling for Stratificatio - Med Ram Verma; Hilal A. Lone; Rajesh Tailor (Journal of the Indian Society of Agricultural Statistics, 2025)
Double sampling for stratification is a statistical technique used in survey sampling to improve the efficiency of estimating population parameters estimates. In the present paper we have proposed a generalized dual to ratio-cum-product type estimator of population mean. The expression for the MSE (Mean Square Error) of the proposed estimator has been derived upto first degree of approximation. The comparison of the proposed estimator with Ige and Tripathi (1987) and Lone et al. (2020) estimators in double sampling for stratification indicated that proposed estimator is more efficient than the other estimators given in the literature. Motivated by Tailor and Lone (2014), the generalised version of the proposed estimator is also suggested in the present paper. The empirical study indicated that the proposed estimator is more efficient than the other estimators